Asthma's effect on brain connectivity and cognitive decline - Wang, Tao; Huang, Xin; Wang, Jun (Frontiers in Neurology, 2023)
Objective: To investigate the changes of dynamic voxel mirror homotopy connection (dVMHC) between cerebral hemispheres in patients with asthma.Methods: Our study was designed using a case-control method. 31 BA subjects and 30 healthy subjects with matching basic information were examined by rsfMRI. Calculate and obtain the dVMHC value between the cerebral cortex.Results: Compared with the normal control group, the dVMHC of lingual gyrus (Ling) and calcarine (CAL), which represented visual network (VN), increased significantly in asthma group, while the dVMHC of medial superior frontal gyrus (SFG), anterior / middle / posterior cingulate gyrus (A/M/PCG) and supplementary Motor Area (SMA) of sensorimotor network decreased significantly in asthma group.Conclusion: This study showed that the ability of emotion regulation and the efficiency of visual and cognitive information processing in BA patients were lower than those in HC group. DVMHC analysis can be used to sensitively evaluate oxygen saturation, visual function changes and attention bias caused by emotional disorders in patients with asthma, as well as to predict airway hyperresponsiveness, inflammatory progression and dyspnea.